Herpes zoster as a marker of occult cancer: A systematic review and meta-analysis. Issue 3 (March 2017) - Schmidt, S.A.J.; Mor, A.; Schønheyder, H.C.; Sørensen, H.T.; Dekkers, O.M.; Cronin-Fenton, D.
Summary: Objectives: Researchers have advocated for an increased awareness of occult cancer among herpes zoster patients, but there are no systematic reviews to support these claims. We therefore conducted a systematic review and meta-analysis of evidence on zoster and risk of occult cancer. Methods: Through February 18, 2016, we searched PubMed, EMBASE and references of relevant papers for studies on zoster and risk of any cancer. One author screened retrieved papers by title and abstract; included papers were reviewed by two authors for eligibility, data extraction, and potential biases. Despite statistical heterogeneity, associations were consistently in the same direction and we therefore computed pooled relative risks using random-effects models. Results: We identified 46 eligible studies, 10 of which considered all cancer types combined. The pooled relative risk for any cancer was 1.42 (95% confidence interval: 1.18, 1.71) overall and 1.83 (95% confidence interval: 1.17, 2.87) at one year after zoster. Considering cancer subtypes, the highest estimates were generally reported for occult hematological cancer. The absolute risk of any cancer at one year after presentation with zoster was 0.7–1.8%. Conclusion: This study supports an association between zoster and occult cancer, but the low absolute risk of cancer limits the clinical implications. Highlights: This systematic review shows that herpes zoster may be a marker of occult cancer. The highest relative risk was found for hematological cancer. The clinical implications are, however, limited by the low absolute risk of cancer. There are no studies on the effectiveness of cancer work-up in persons with zoster.